Virus taxonomy : (Elsevier Academic Press, 2005)
This is the standard and definitive reference for virus taxonomy, generated by the ICTV approximately every 3 years. The VIII ICTV "Virus Taxonomy" Report provides information on 3 orders of viruses, 73 families, 9 subfamilies, 287 genera and 1938 virus species, illustrated by more than 429 pictures and diagrams, most of them in color. It is the standard official ITCV reference for virus taxonomy and nomenclature, compiling data from 500 international experts. It covers over 6000 recognized viruses, organized by family with diagrams of genome organization and virus replication cycle. It provides data on the phylogenic relationships between viruses belonging to the same or different taxanomy and now includes information about the qualitative and quantitative relationships between virus sequences.